GAMBARAN KOMUNIKASI KERJA, KEPUASAN KERJA DAN KINERJA KARYAWAN TOSERBA YOGYA CABANG SUNDA BANDUNG - Nurfitrianti, Marisa; Sumiyati, Sumiyati; Widjajanta, Bambang (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - The purpose of this study is to knowing the description of working communiacation, job satisfaction and employee performance. Design/methodology/approachh - The design of this study was cross sectional. This research uses descriptive approach with explanatory survey method. A total of 57 respondents were selected using probability sampling. A questionnaire was used as a research instrument to collect data from respondents. Analytical technique used is descriptive technique by using frequency distribution.Findings - Based on the results of the research using descriptive analysis, the results indicate that the description of working communication is in effective category according to score of representative 81,3%, job satisfaction is in high category according to score of representative 79,3 %Â , and employee performance is in high category according to score of representative 77,8%. Originality/value -Â This study provides a basis for understanding issues of working Â communication, job satisfaction, and employee performance. The difference of this study with the previous research is located on the object which is the company in the retail industry that is Toserba Yogya Cabang Sunda Bandung, with the variables studied namely working communication, job satisfaction, and employee performances, and using different theory or reference from previous researcher.